Magnetic control graphene foam wave-absorbing material and preparation method thereof

By compounding graphene with magnetic microspheres and using improved genetic algorithms for electromagnetic optimization design, the problem of difficult balance between impedance matching and electromagnetic attenuation capabilities of existing graphene absorbing materials is solved, and a significant improvement in absorbing performance is achieved.

CN120186981APending Publication Date: 2025-06-20SHENYANG AEROSPACE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510229059.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

It is difficult for existing graphene absorbing materials to balance impedance matching and electromagnetic attenuation capabilities, which affects their absorbing performance.

Method used

By compounding graphene with magnetic microspheres and using improved genetic algorithms to perform electromagnetic optimization design of multi-layer composite structures, an optimized wave absorbing structure and performance modification strategy is established to obtain magnetron graphene foam multi-layer composite wave absorbing material with excellent wave absorbing performance.

Benefits of technology

A good balance between impedance matching and electromagnetic attenuation capability is achieved, which significantly improves wave absorption performance, especially in the 1-18GHz frequency range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120186981A_ABST
    Figure CN120186981A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of microwave absorption functional materials, and particularly provides a magnetically-controlled graphene foam wave-absorbing material and a preparation method thereof.The method comprises the steps that oxidized graphene and magnetic microspheres serve as base materials, and magnetically-controlled graphene foam with the adjustable type and content of loaded magnetic microspheres is constructed through a solvothermal method; the method comprises the following steps: establishing a material database based on dielectric constants and magnetic conductivity of magnetically-controlled graphene foams, randomly screening magnetically-controlled graphene foams with different components and thicknesses to construct a multi-layer composite wave-absorbing material, encoding to obtain initial genetic individuals, and establishing an initial population; a fitness function is constructed by taking the reflection loss and the effective absorption bandwidth of genetic individuals in an initial population as variables, optimization iteration is performed according to a dynamic threshold value, and the magnetic control graphene foam multilayer composite wave-absorbing material with the optimal wave-absorbing performance is obtained and has the advantages of being light in weight, compressible, excellent in wave-absorbing performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microwave absorption functional materials, and particularly relates to a magnetically controlled graphene foam microwave absorption material and a preparation method thereof. Background Art

[0002] With the continuous advancement of information globalization technology, the rapid development and popularization of 5G communication technology have brought many conveniences to people's lives and work. However, the increasingly serious electromagnetic wave interference and electromagnetic pollution not only affect human health, but also interfere with precision electronic instruments and shorten their service life, posing a serious threat to fields such as life, information, and national defense security. Radar absorbing materials can not only eliminate or reduce electromagnetic interference and reduce electromagnetic leakage, but also effectively reduce the radar cross-section of targets and avoid radar tracking, greatly improving the combat performance and service safety of military equipment. Therefore, it is urgent to develop new absorbing materials with comprehensive properties of "thin, wide, light, and strong".

[0003] Three-dimensional graphene porous foam materials have realized the functional expansion of the excellent properties of two-dimensional graphene from the micro-nano scale to the three-dimensional macro scale, and their unique structural advantages show great application potential in the field of electromagnetic wave absorbing materials. The rich pores of graphene foam can not only effectively avoid the self-accumulation of graphene sheets, but also reduce the dielectric constant of graphene and increase the interfacial polarization effect, which is beneficial to the multiple reflection, scattering, and attenuation of electromagnetic waves. However, the high conductivity of graphene often leads to poor impedance matching characteristics, which is not conducive to the entry of electromagnetic waves into the material for attenuation loss. Therefore, how to balance the relationship between its impedance matching and electromagnetic attenuation ability remains a challenge. Summary of the Invention

[0004] In view of this, the present invention provides a magnetically controlled graphene foam microwave absorption material optimized and designed based on a genetic algorithm and a preparation method thereof. This method constructs magnetically controlled graphene foam by loading magnetic microspheres with graphene as the base template, and uses an improved genetic algorithm to conduct electromagnetic optimization design for the magnetically controlled graphene foam, establishing an optimizable wave absorption structure and performance modification strategy to obtain a magnetically controlled graphene foam multi-layer composite wave absorption material with excellent wave absorption performance.

[0005] The present invention provides a magnetically controlled graphene foam microwave absorption material optimized and designed based on a genetic algorithm and a preparation method thereof, including the following steps:

[0006] (1) Prepare a solution by mixing 0.2 - 2 g of metal salt with 60 - 150 ml of a mixed solvent composed of isopropanol, glycerol, and deionized water, inject it into a reaction kettle, and react at a temperature of 120 - 200 °C for 8 - 15 h. After centrifugal separation, alcohol washing, drying, and high-temperature calcination, magnetic metal microspheres are obtained for standby.

[0007] The metal salt is one or more of iron nitrate, cobalt nitrate, nickel nitrate, zinc nitrate, iron chloride, cobalt chloride, nickel chloride, zinc chloride, iron acetylacetonate, cobalt acetylacetonate, and nickel acetylacetonate.

[0008] (2) Prepare graphene oxide according to the Hummers method, configure a graphene oxide / ethanol solution with a concentration of 2 - 10 mg / ml, add 10 - 150 mg of the magnetic microspheres described in step (1), ultrasonically disperse for 10 - 50 min and mix evenly, then inject into a reaction kettle and react at a temperature of 120 - 200 °C for 6 - 15 h. After soaking, washing with water, and freeze-drying, a magnetically controlled graphene foam with adjustable types and contents of loaded magnetic microspheres is obtained.

[0009] (3) Based on the dielectric constant and magnetic permeability of the magnetically controlled graphene foam described in step (2), establish a material database, randomly screen magnetically controlled graphene foams with different components and thicknesses from it to construct a multi-layer composite absorbing material and encode it to obtain an initial genetic individual, and form an initial population.

[0010] The initial genetic individual is as follows: Represent magnetically controlled graphene foams with different components using two-digit decimal encoding respectively, represent magnetically controlled graphene foams with different thicknesses using four-digit decimal encoding respectively, link the two-digit decimal encoding representation corresponding to each layer of magnetically controlled graphene foam material with the four-digit decimal encoding representation to form the encoding representation of each layer of material, and link the encoding representations of each layer of material to obtain the encoding representation of the initial genetic individual.

[0011] (4) Set the dynamic threshold as the optimization constraint condition, construct a fitness function with the reflection loss and effective absorption bandwidth of the genetic individuals in the initial population described in step (3) as variables, use the elitist retention method to screen out elite individuals with large fitness, perform random crossover and mutation on them to generate a new generation of population, and through repeated optimization iterations according to the optimal threshold, obtain a magnetically controlled graphene foam multi-layer composite absorbing material with the best absorbing performance.

[0012] The optimization constraint condition is the dynamic threshold set through the population: that is, the optimal threshold of the Nth generation population is lower than the minimum reflectivity of the (N - 1)th (N > 1) generation and greater than the effective absorption bandwidth of the (N - 1)th (N > 1) generation;

[0013] The fitness function S constructed with the reflection loss and effective absorption bandwidth of the genetic individuals in the initial population as variables is as follows:

[0014] S = ω1·BW - ω2·RL min

[0015] where BW is the effective absorption bandwidth when the reflection loss of the multi-layer absorbing material is lower than -10 dB in the frequency range of 1 - 18 GHz; RL minis the minimum reflection loss of the multi-layer microwave absorbing material in the frequency range of 1-18 GHz; ω1 and ω2 are weight coefficients, which are used to balance the influence of bandwidth and reflection loss in the fitness function respectively;

[0016] The elite retention method is as follows: the elite individuals with large fitness values selected are directly copied to the next generation without paired crossover, and then the individuals with reflection loss values and bandwidth errors within 5% of the elite individuals are selected again to participate in the crossover and mutation of the new generation;

[0017] The transmission line principle is used to calculate the reflection loss value of the multi-layer microwave absorbing material. The formula includes:

[0018] Z inn =Z n *(Z inn-1 +Z n *tanh(r n *d n )) / (Z n +Z inn-1 *tanh(r n *d n ))

[0019] Among them, Z inn represents the input impedance of the nth layer of material, d n represents the thickness of the nth layer of material, and r n represents the transmission coefficient of the nth layer of material;

[0020]

[0021] λ0 is the wavelength of the incident electromagnetic wave, and ε N and μ N are the intrinsic permittivity and permeability of the nth layer respectively;

[0022]

[0023] Z n represents the characteristic impedance, and ε0 and μ0 are the vacuum permittivity and vacuum permeability respectively;

[0024]

[0025] RL=20logR

[0026] R is the reflection coefficient, and RL represents the reflection loss.

[0027] Compared with the prior art, the beneficial effects of the present invention are:

[0028] (1) The magnetically controlled graphene foam prepared by the present invention realizes a good balance between impedance matching and attenuation constant by compounding graphene with magnetic microspheres. The electromagnetic parameters of the graphene foam can be effectively regulated by adjusting the types and contents of the magnetic microspheres, and it has more excellent microwave absorption performance than single graphene or magnetic wave absorbers.

[0029] (2) The present invention uses an improved genetic algorithm to conduct electromagnetic optimization design for the multi-layer composite absorbing structure of the magnetically controlled graphene foam, so that the minimum reflection loss value and the effective absorption bandwidth are significantly improved compared with the single-layer graphene foam.

[0030] (3) The multi-layer composite absorbing material of the magnetically controlled graphene foam designed by the present invention has the advantages of light weight, compressibility, and excellent microwave absorption performance, and has important application prospects in the field of lightweight and high-efficiency microwave absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic flow chart of the present invention;

[0032] Figure 2 is an X-ray diffraction spectrum of the magnetically controlled graphene foam prepared in Example 1 of the present invention;

[0033] Figure 3 is a scanning electron microscope image of the magnetically controlled graphene foam prepared in Example 1 of the present invention;

[0034] Figure 4 is a reflection loss curve graph of the magnetically controlled graphene foam prepared in Example 1 of the present invention.

[0035] Figure 5 is a reflection loss curve graph of the magnetically controlled graphene foam prepared in Example 2 of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0036] The principles and features of the present invention will be described below in conjunction with the attached Figures 1-5 The embodiments are only used to explain the present invention and are not intended to limit the scope of the present invention.

[0037] Example 1

[0038] Step 1: Put 0.2 g of Fe(NO3)3·9H2O, 52.5 ml of isopropanol, 7.3 ml of glycerol, and 1 ml of deionized water into a beaker, ultrasonically treat for 20 minutes to obtain a mixed reaction solution, inject it into a 150 ml hydrothermal reaction kettle, react at a temperature of 190 °C for 12 h, after the reaction is completed, perform centrifugal separation, alcohol washing, and drying, transfer the product to a boat in a tube furnace, calcine at 350 °C for 3 h under argon protection, and wait for natural cooling to room temperature to obtain magnetic Fe3O4 hollow microspheres.

[0039] Step 2: Place 2.0 g of flake graphite and 50 ml of concentrated H2SO4 in a 500 ml three-necked flask, stir evenly in an ice-water bath at 0 °C, and slowly add 6.0 g of potassium permanganate in batches. Control the reaction system temperature to be maintained between 0 - 5 °C for 2 h, then transfer it to a water bath at 35 °C and continue the reaction for 3 h. After the reaction is completed, slowly add 100 ml of distilled water and react in a 95 °C water bath for 0.5 h. Finally, add 100 ml of distilled water and 15 ml of H2O2. Wash the product with 10% HCl and distilled water until the pH = 6 - 7, then replace the water in the solution with ethanol through high-speed centrifugation, and obtain a graphene oxide / ethanol solution with a concentration of 6 mg / ml through ultrasonic treatment.

[0040] Take 12 ml of the above graphene oxide / ethanol solution, add the magnetic Fe3O4 microspheres (30 mg, 45 mg, 60 mg, 57 mg, and 90 mg) in Step 1 respectively, and mix evenly by ultrasonic treatment. Inject it into a reaction kettle and react at 180 °C for 12 h. After the reaction is completed, take out the gel body, soak it in deionized water until the ethanol is completely replaced, and then obtain three-dimensional graphene foams loaded with Fe3O4 hollow microspheres with different contents (labeled as S1, S2, S3, S4, and S5) through freeze-drying.

[0041] Figure 2 To prepare the X-ray diffraction pattern of the three-dimensional graphene foam loaded with Fe3O4 hollow microspheres Figure 3 For the scanning electron microscope image of the three-dimensional graphene foam loaded with Fe3O4 hollow microspheres. Figure 2 The peak positions of each diffraction peak in it are consistent with the standard card peak positions of Fe3O4 crystals, indicating the successful preparation of Fe3O4; from Figure 3 it can be seen that Fe3O4 hollow microspheres are evenly attached to the porous network structure of the three-dimensional graphene foam, and there is no obvious agglomeration phenomenon.

[0042] Step 3: Heat the paraffin until it melts, infiltrate the magnetically controlled graphene foam prepared in Step 2, heat it in a vacuum environment at 90 °C for 0.5 h until the infiltration is complete, and then load it into a ring mold to prepare a ring-shaped cylinder with an outer diameter of 7 mm and an inner diameter of 3.04 mm. Use a vector network analyzer to measure its dielectric constant and magnetic permeability, and establish a material database based on the magnetically controlled graphene foam loaded with Fe3O4 microspheres with different contents and its dielectric constant and magnetic permeability.

[0043] Randomly select three magnetically controlled graphene foam materials from the material database, and construct a three-layer composite absorbing material according to random thicknesses. The thickness of a single layer is set to 0.4 - 2.0 mm, and the total thickness is set to 1.2 - 6.0 mm. Add the composite absorbing materials that meet the requirements to the initial population. Set the initial population size to 150. When constructing the three-layer composite absorbing material, 450 magnetically controlled graphene foam materials with different components and thicknesses need to be randomly selected from the material database for random combination. Represent the magnetically controlled graphene foam with different components using two-digit decimal coding, and represent the magnetically controlled graphene foam with different thicknesses using four-digit decimal coding. Link the two-digit decimal coding representation corresponding to each layer of magnetically controlled graphene foam material with the four-digit decimal coding representation to form the coding representation of each layer of material. Link the coding representations of each layer of material to obtain the coding representation of the initial genetic individual. Randomly combine the coding of every 3 single-layer materials to obtain 150 initial genetic individual codings, thereby forming the initial population.

[0044] Step 4: Define the fitness function S with the reflection loss and effective absorption bandwidth of the genetic individuals in the initial population as variables

[0045] S = ω1·BW - ω2·RL min

[0046] where BW is the effective absorption bandwidth when the reflection loss of the multi-layer composite absorbing material is lower than -10 dB in the frequency range of 1 - 18 GHz; RL min is the minimum reflection loss of the multi-layer composite absorbing material in the frequency range of 1 - 18 GHz; ω1 and ω2 are weight coefficients, which are used to balance the influence of bandwidth and reflection loss in the fitness function respectively. It can be seen that the larger the value of S, the wider the effective absorption bandwidth and the smaller the reflection loss value of the corresponding individual, that is, the better the wave absorption performance.

[0047] Evaluate the fitness of genetic individuals by calculating the fitness function S. Use the elitist retention method to select the genetic individuals with large fitness. The elite individuals with large fitness are directly copied to the next generation without paired crossover, and then the individuals with a reflection loss value and bandwidth error within 5% of the elite individuals are selected again to participate in the crossover and mutation of the new generation. The probabilities of crossover and mutation are 0.8 and 0.1 respectively.

[0048] Set a dynamic threshold for the population: that is, the optimal threshold for the Nth generation population is lower than the minimum reflectivity of the N - 1 (N > 1) generation and greater than the effective absorption bandwidth of the N - 1 (N > 1) generation. The calculation formula for the reflection loss value of individuals in each generation of the population is:

[0049] Z inn = Z n *(Z inn-1 + Z n*tanh(r n *d n )) / (Z n +Z inn-1 *tanh(r n *d n ))

[0050] Among them, Z inn represents the input impedance of the nth layer of material, d n represents the thickness of the nth layer of material, and r n represents the transmission coefficient of the nth layer of material;

[0051]

[0052] λ0 is the wavelength of the incident electromagnetic wave, ε N and μ N are the intrinsic permittivity and permeability of the nth layer, respectively;

[0053]

[0054] Z n represents the characteristic impedance, and ε0 and μ0 are the permittivity of free space and the permeability of free space, respectively;

[0055]

[0056] RL = 20logR

[0057] R is the reflection coefficient, and RL represents the reflection loss.

[0058] Taking the dynamic threshold as the optimization constraint condition, judge whether the elite individuals selected by the elite retention method meet the optimal threshold. Retain the elite individuals that meet the optimal threshold and use them as the current optimal elite individuals. Continuously update the optimal elite individuals through repeated optimization iterations. When the number of iterations reaches 450 times, the optimization ends, and the final optimal elite individuals, that is, the magnetically controlled graphene foam multi-layer composite absorbing material with the best wave absorption performance, are obtained.

[0059] Analysis of optimization results:

[0060] When the target total thickness is 2.3 mm, the best combination obtained is: graphene foam (S3) containing 60 mg of magnetic Fe3O4 microspheres with a thickness of 1.2 mm, graphene foam (S1) containing 30 mg of magnetic Fe3O4 microspheres with a thickness of 0.6 mm, and graphene foam (S2) containing 45 mg of magnetic Fe3O4 microspheres with a thickness of 0.5 mm. Among them, 1.2 mm of S3 is the top layer, and 0.5 mm of S2 is the bottom layer. As Figure 4As shown in the figure, the performance of the magnetically controlled graphene foam multi-layer composite microwave absorbing material obtained after optimization is as follows: the reflection loss value is lower than -10 dB in the frequency band of 11.54 - 17.07 GHz, the peak value of the reflection loss reaches -58.59 dB at 13.92 GHz, and the minimum reflection loss value and the effective absorption bandwidth are significantly improved compared with the single-layer magnetically controlled graphene foam with the same thickness.

[0061] Example 2

[0062] Step 1: 0.4 g of Fe(NO3)3·9H2O, 0.5 g of Co(NO3)2·6H2O, and 0.4 g of Ni(NO3)2·6H2O were respectively placed in a beaker with 105 ml of isopropanol, 14.6 ml of glycerol, and 2 ml of deionized water, and ultrasonically treated for 20 minutes to obtain a mixed reaction solution, which was injected into a hydrothermal reaction kettle and reacted at 190 °C for 12 h. After the reaction, it was centrifuged, washed with alcohol, and dried. The product was transferred to a boat in a tubular furnace and calcined at 350 °C for 3 h under argon protection. After natural cooling to room temperature, magnetic Fe3O4, Co3O4, and NiO hollow microspheres were obtained respectively.

[0063] Step 2: 2.0 g of flake graphite and 50 ml of concentrated H2SO4 were placed in a 500 ml three-necked flask, stirred evenly in an ice-water bath at 0 °C, and 6.0 g of potassium permanganate was added slowly in batches, controlling the reaction system temperature to be maintained between 0 - 5 °C for 2 h, and then transferred to a water bath at 35 °C to continue the reaction for 3 h. After the reaction, 100 ml of distilled water was slowly added dropwise and reacted in a water bath at 95 °C for 0.5 h. Finally, 100 ml of distilled water and 15 ml of H2O2 were added. The product was washed with 10% HCl and distilled water until the pH = 6 - 7, and then the water in the solution was replaced with ethanol by high-speed centrifugation, and then ultrasonically treated to obtain a graphene oxide / ethanol solution with a concentration of 5 mg / ml.

[0064] Take 15 ml of the above graphene oxide / ethanol solution, and add the magnetic Fe3O4 hollow microspheres (30, 45, 60, 75, and 90 mg) in Step 1 respectively, ultrasonically mix evenly, inject into the reaction kettle and react at 180 °C for 12 h. After the reaction, take out the gel, soak it in deionized water until the ethanol is completely replaced, and then obtain three-dimensional graphene foams loaded with different contents of Fe3O4 hollow microspheres (labeled as F1, F2, F3, F4, and F5) by freeze-drying.

[0065] Take 15 ml of the above graphene oxide / ethanol solution, and add the magnetic Co3O4 hollow microspheres (70, 90, 120 mg) in Step 1 respectively. Ultrasonically mix them evenly, inject them into the reaction kettle, and react at 180 °C for 12 h. After the reaction is completed, take out the gel, soak it in deionized water until the ethanol is completely replaced, and then obtain three-dimensional graphene foam loaded with Co3O4 hollow microspheres (labeled as C1, C2, C3) by freeze-drying.

[0066] Take 15 ml of the above graphene oxide / ethanol solution, and add the magnetic NiO hollow microspheres (18, 36, 72, 144 mg) in Step 1 respectively. Ultrasonically mix them evenly, inject them into the reaction kettle, and react at 180 °C for 12 h. After the reaction is completed, take out the gel, soak it in deionized water until the ethanol is completely replaced, and then obtain three-dimensional graphene foam loaded with NiO hollow microspheres (labeled as N1, N2, N3, N4) by freeze-drying.

[0067] Step 3: Heat the paraffin until it melts, infiltrate the magnetically controlled graphene foam prepared in Step 2, heat it in a vacuum environment at 90 °C for 0.5 h until the infiltration is complete, and then load it into a ring mold to prepare a ring-shaped cylinder with an outer diameter of 7 mm and an inner diameter of 3.04 mm. Use a vector network analyzer to measure its dielectric constant and magnetic permeability, and establish a material database of graphene foam loaded with different types and contents of magnetic microspheres and their dielectric constants and magnetic permeabilities.

[0068] Randomly select four magnetically controlled graphene foam materials from the material database, and construct a four-layer composite absorbing material according to random thicknesses. The thickness of each layer is set to 0.4 - 1.0 mm, and the total thickness is set to 1.6 - 4.0 mm. Add the composite absorbing materials that meet the requirements to the initial population. Set the number of the initial population to 200. When constructing the four-layer composite absorbing material, 800 magnetically controlled graphene foam materials with different components and thicknesses need to be randomly selected from the material database for random combination. Represent the magnetically controlled graphene foam with different components using two-digit decimal codes respectively, represent the magnetically controlled graphene foam with different thicknesses using four-digit decimal codes respectively. Link the two-digit decimal code representation and the four-digit decimal code representation corresponding to each layer of magnetically controlled graphene foam material to form the code representation of each layer of material. Link the code representations of each layer of material to obtain the code representation of the initial genetic individual. Randomly combine the code representations of every 4 single-layer materials to obtain 200 initial genetic individual codes, thus forming the initial population.

[0069] Step 4: Define a fitness function S with the reflection loss and effective absorption bandwidth of the genetic individuals in the initial population as variables

[0070] S = ω1·BW - ω2·RL min

[0071] Among them, BW is the effective absorption bandwidth when the reflection loss of the multi-layer composite absorbing material is lower than -10 dB in the frequency range of 1 - 18 GHz; RL min is the minimum reflection loss of the multi-layer composite absorbing material in the frequency range of 1 - 18 GHz; ω1 and ω2 are weighting coefficients, which are used to balance the influence of bandwidth and reflection loss in the fitness function. It can be seen that the larger the value of S, the wider the effective absorption bandwidth and the smaller the reflection loss value of the corresponding individual, that is, the better the wave absorption performance.

[0072] By calculating the fitness function S, the fitness degree of genetic individuals is evaluated. The elite retention method is used to screen out the genetic individuals with large fitness. The elite individuals with large fitness are directly copied to the next generation without paired crossover, and then the individuals with a reflection loss value and bandwidth error within 5% of the elite individuals are screened out again to participate in the crossover and mutation of the new generation. The probabilities of crossover and mutation are 0.8 and 0.1 respectively.

[0073] A dynamic threshold is set for the population: that is, the optimal threshold of the Nth generation population is lower than the minimum reflectivity of the N - 1 (N > 1) generation and greater than the effective absorption bandwidth of the N - 1 (N > 1) generation. The calculation formula for the reflection loss value of each individual in each generation of the population is:

[0074] Z inn =Z n *(Z inn-1 +Z n *tanh(r n *d n )) / (Z n +Z inn-1 *tanh(r n *d n ))

[0075] Among them, Z inn represents the input impedance of the nth layer of material, d n represents the thickness of the nth layer of material, r n represents the transmission coefficient of the nth layer of material;

[0076]

[0077] λ0 is the wavelength of the incident electromagnetic wave, ε N and μ N are the intrinsic permittivity and permeability of the nth layer respectively;

[0078]

[0079] Z n represents the characteristic impedance, ε0 and μ0 are the vacuum permittivity and vacuum permeability respectively;

[0080]

[0081] RL = 20logR

[0082] R is the reflection coefficient, and RL represents the reflection loss.

[0083] Taking the dynamic threshold as the optimization constraint condition, it is judged whether the elite individuals screened by the elitist retention method meet the optimal threshold. The elite individuals that meet the optimal threshold are continuously retained and used as the current optimal elite individuals. The optimal elite individuals are continuously updated through repeated optimization iterations. When the number of iterations reaches 800 times, the optimization ends, and the final optimal elite individuals are obtained, that is, the magnetically controlled graphene foam multi-layer composite absorbing material with the best absorbing performance.

[0084] Analysis of optimization results:

[0085] When the target total thickness is 2.9 mm, the best combination obtained is: graphene foam (F2) containing 45 mg of magnetic Fe3O4 microspheres with a thickness of 0.6 mm, graphene foam (C2) containing 90 mg of magnetic Co3O4 microspheres with a thickness of 0.8 mm, graphene foam (N2) containing 36 mg of magnetic NiO microspheres with a thickness of 1 mm, and graphene foam (F4) containing 75 mg of magnetic Fe3O4 microspheres with a thickness of 0.5 mm, where 0.6 mm of F2 is the top layer and 0.5 mm of F4 is the bottom layer. As Figure 5 shown, the performance of the magnetically controlled graphene foam multi-layer composite absorbing material obtained after optimization is: the reflection loss value is lower than -10 dB in the frequency band of 9.67 - 18 GHz, and the peak reflection loss reaches -56.17 dB at 13.58 GHz, and the effective absorption bandwidth is further improved.

[0086] The above embodiments only express the implementation manners of the present invention, but should not be construed as limiting the scope of the patent of the present invention. It should be noted that for those skilled in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention.

Claims

1. A method for preparing a magnetron graphene foam absorbing material, characterized in that: The following steps are involved: (1) preparing a solution of 0.2-2 g of a metal salt and 60-150 ml of a mixed solvent consisting of isopropanol, glycerol and deionized water, injecting the solution into a reaction kettle and reacting the solution at 120-200° C. for 8-15 h, and obtaining magnetic metal microspheres after centrifugal separation, alcohol washing, drying and high-temperature calcination for later use; (2) preparing graphene oxide according to the Hummers method, preparing a graphene oxide / ethanol solution with a concentration of 2-10 mg / ml, adding 10-150 mg of magnetic microspheres and ultrasonically dispersing for 10-50 min to mix evenly, injecting into a reactor and reacting at a temperature of 120-200° C. for 6-15 h, and obtaining a magnetically controlled graphene foam with adjustable type and content of loaded magnetic microspheres after soaking, washing, and freeze-drying; (3) establishing a material database based on the dielectric constant and magnetic permeability of the above-mentioned magnetron graphene foam, randomly selecting magnetron graphene foams of different components and thicknesses to construct a multilayer composite absorbing material and encoding them to obtain initial genetic individuals to form an initial population; (4) The dynamic threshold is set as the optimization constraint condition, and the reflection loss and effective absorption bandwidth of the genetic individuals in the initial population are used as variables to construct the fitness function. The elite retention method is used to screen out elite individuals with high fitness, and random crossover and mutation are performed on them to generate a new generation of population. According to the optimal threshold, repeated optimization and iteration are performed to obtain the magnetically controlled graphene foam multilayer composite absorbing material with the best absorbing performance.

2. The method for preparing a magnetron graphene foam absorbing material according to claim 1, characterized in that: The metal salt is one or more of ferric nitrate, cobalt nitrate, nickel nitrate, zinc nitrate, ferric chloride, cobalt chloride, nickel chloride, zinc chloride, ferric acetylacetonate, cobalt acetylacetonate, and nickel acetylacetonate.

3. The method for preparing a magnetron graphene foam absorbing material according to claim 1, characterized in that: The coding of multi-layer composite absorbing materials is as follows: The magnetically controlled graphene foams of different components are represented by two-digit decimal codes, and the magnetically controlled graphene foams of different thicknesses are represented by four-digit decimal codes. The two-digit decimal code representation corresponding to each layer of the magnetically controlled graphene foam material is linked with the four-digit decimal code representation to form the code representation of each layer of the material. The code representation of each layer of the material is linked to obtain the code representation of the initial genetic individual.

4. The method for preparing a magnetron graphene foam absorbing material according to claim 1, characterized in that: The dynamic threshold is the optimal threshold of the Nth generation population, which is lower than the minimum reflectivity of the N-1 (N>1) generation and greater than the effective absorption bandwidth of the N-1 (N>1) generation.

5. The method for preparing a magnetron graphene foam absorbing material according to claim 1, characterized in that: The fitness function S is: S=ω1·BW-ω2·RL min Where BW is the effective absorption bandwidth of the multilayer absorbing material when the reflection loss is less than -10dB in the frequency range of 1-18GHz; RL min is the minimum reflection loss of the multilayer absorbing material in the frequency range of 1-18 GHz; ω1 and ω2 are weight coefficients, which are used to balance the influence of bandwidth and reflection loss in the fitness function respectively.

6. The method for preparing a magnetron graphene foam absorbing material according to claim 1, characterized in that: The elite retention method is specifically as follows: the elite individuals with high fitness are directly copied to the next generation without pairing and crossover, and then the individuals whose reflection loss values ​​and bandwidth errors are within 5% of the elite individuals are screened out again to participate in the crossover and mutation of the new generation.

7. The method for preparing a magnetron graphene foam absorbing material according to claim 1, characterized in that: The reflection loss value of multi-layer absorbing materials is calculated using the transmission line principle. The formula includes: Z inn =Z n *(Z inn-1 +Z n *tanh(r n *d n )) / (Z n +Z inn-1 *tanh(r n *d n )) Among them, Z inn represents the input impedance of the nth layer of material, d n represents the thickness of the nth layer of material, r n represents the transmission coefficient of the nth layer of material; λ0 is the wavelength of the incident electromagnetic wave, ε N and μ N are the intrinsic permittivity and magnetic permeability of the nth layer, respectively; Z n represents characteristic impedance, ε0 and μ0 are vacuum dielectric constant and vacuum magnetic permeability respectively; RL=20logR R is the reflection coefficient and RL represents the reflection loss.

8. A magnetron graphene foam absorbing material, characterized in that: The material is prepared by the method described in any one of claims 1 to 7.